Pemberdayakan Kompetensi Guru dalam Penguatan Model Pembelajaran Cooperative Learning Siswa di SDN Kenari 07 Pagi - Abdul Halim; Ainur Rosyid; Alberth Supriyanto Manurung (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
Cooperative Learning is a model of logic regarding the form, arrangement, magnitude and concepts related to each other. The concept is always related to everyday human life. Cooperative Learning in the form of Empowering Teacher Competencies in Strengthening Cooperative Learning Models Students not only increase curiosity but always develop according to the times, Cooperative Learning is a model that aims to instill and develop the learning process in teachers. Based on the results of observations at SDN Kenari 07 Pagi in the learning process, teachers still use conventional or teacher-centered teaching methods as information providers, with the literacy movement students are expected to improve the good quality of each problem-solving concept in the form of application questions. The purpose of this community service activity for PKM is Empowering Teacher Competence in Strengthening Cooperative Learning Learning Models is to increase knowledge which changes from time to time. The subjects of this community service are all students at SDN Kenari 07 Pagi.